Analisis Implementasi 9 Instrumen Akreditasi Perpustakaan Sekolah Terakreditasi A : Studi Kasus Madrasah Aliyah Darul Ulum Banda Aceh - Siti Aminah; Ade Nufus; Mutia Watul Wardah; Cut Putroe Yuliana (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
Introduction. This study aims to evaluate the implementation of the nine library accreditation instruments at the MA Darul Ulum Banda Aceh library, which has received an A accreditation rating. The quality of library services is the main focus, as it support the teaching and learning process and contributed to achieving national standards. Data Collection Methods. The research employs a cased study approach, involving semi structured interviews, observations, and documentation analysis of accreditation forms. Data Analysis. The results show that the library successfully achieved a total score of 92.02 out of 100, indicating excellent service quality, particularly in the areas of library services and management. Results and Discussion.The highest scores were achieved in the service and library management components, while collection development and librarian competency remain the main challenges due to budget limitations and the need for continuous professional training. Various innovations, including literacy programs, reading communities, and improved library services, have contributed to strengthening the library's role as an active learning center and enhancing the quality of educational services. The main challenges identified include limited collection development due to budget constraints and the need to enhance staff competencies of library staff through continuous training. Innovations such us form of literacy activities and the establishment of reading communities also helped strengthen the library's role as an active learning center. Conclusion.This study concludes that the implementation of the nine library accreditation instruments has been effective; however, continuous improvement in collection development, librarian competencies, and service innovation is essential to maintain and enhance library quality.